Chemical ordering suppresses large-scale electronic phase separation in doped manganites - Yinyan Zhu (Nature Portfolio, 2016)
In oxide materials, cation doping strongly influences the electronic correlations which promote diverse phenomena such as colossal magnetoresistance and superconductivity. Here, the authors use magnetic microscopy to image the effects of spatially ordered doping on electronic phase separation in oxide superlattices.